(untitled) (Comprehensive Journal of Science, 2026)
This research presents an in-depth foundational study on "Supplication (Dua) and its Impact on a Muslim’s Life," as it represents the fundamental pillar of worship and the spiritual bridge connecting human frailty with Divine Omnipotence. The study stems from a central problematic: How does the jurisprudence of Dua contribute to shaping a balanced Islamic personality amidst contemporary materialistic challenges? The researcher employed a descriptive-analytical methodology, dividing the study into three integrated chapters. Chapter One provides a semantic and legal foundation for the term "Dua" in the Quran and Sunnah. Chapter Two delves into the "psychology of supplication" and the jurisprudence of response, reviewing conditions, etiquettes, and the profound impact of supplication on psychological security and inner peace. Chapter Three is dedicated to addressing complex contemporary issues, such as the dialectic relationship between Divine Decree (Qadar) and Dua, the controversies surrounding collective supplication, and the rulings on dedicating rewards to the deceased.